A free-rotating ball-shaped transmitting coil with wireless power transfer system for robot joints. Issue 1 (12th February 2019) - Yang, Yang; Chen, Wenjie; Dai, Liyu; Wang, Rui
Abstract : Wireless power transmission (WPT) systems with moveable mechanical parts have been acquired more and more attention during the past decade. However, due to the moveable feature of transmitting coil and receiving coil, misalignment issue lead to extra power loss, decrease in efficiency, increase in control complexity, and unwanted performance degradation of the whole system. Moreover, it happened frequently than those traditional planar coils systems. The motivation for this paper is trying to have a deep understanding of quantitative relationship between ball-shaped coils mutual inductance and misalignment. Based upon that, engineers would know more detail of the coils position and mutual inductance. So, optimized design might be achieved. On considering that, this paper presents a WPT system with a ball-shaped coil for robot joints. A mutual inductance calculation based on filament method aimed at ball-shaped coil is proposed. Based on these, nine different ball-shaped coil solutions are calculated. Then, model with a minimized change rate of mutual inductance against the angular misalignment is chosen as the optimized design. Circuit analysis of the WPT system with the series–series resonant topology is conducted to choose a proper working frequency and load. Finally, an experimental platform is established. It demonstrates the feasibility of the proposed calculation method and the feasibility of the WPT prototype.